RELIGIOSITY IN ACEH: THE DIVERSITY MEANING OF PARTICIPATION IN SALAT Al-JAMA'AH (CONGREGATIONAL PRAYER) FOR INSTITUTIONAL MUSLIM EMPLOYEES GOVERNMENT OF ACEH TAMIANG: RELIGIOSITY IN ACEH: THE DIVERSITY MEANING OF PARTICIPATION IN SALAT Al-JAMA'AH (CONGREGATIONAL PRAYER) FOR INSTITUTIONAL MUSLIM EMPLOYEES GOVERNMENT OF ACEH TAMIANG - Nina Afrida; Syarifah Mudrika Mudrika; Nina Rahayu (Fakultas Agama Islam Universitas Wiralodra, 2021)
Congregational prayer for Acehnese government employees has been regulated in qanun number 11 of 2002. In its implementation, this qanun receives a positive response in Aceh Tamiang regency, so that many employees implemented it. According to dramaturgy theory, this implementation could have various meanings. The objective of this study is to find out how Aceh Tamiang Muslim employees interpret their participation, either pray in a congregation at the office or individual prayer (munfarid). This study uses a qualitative approach with ethnographic type. The results of this study indicate that muslim employees have different interpretations of their participation in congregational prayers. Some of them feel calmer besides getting multiple rewards of praying in the congregation. Congregational prayer is also a gathering moment in which they can interact socially with fellow congregations so that associative meanings can appear which the results are cooperation, assimilation, and negotiation. However, some choose to perform individual prayer (munfarid) for certain reasons.